Antiulcer Effect of Honey in Nonsteroidal Anti-Inflammatory Drugs Induced Gastric Ulcer Model in Rats: A Systematic Review. (15th July 2018) - Fazalda, Annuar; Quraisiah, Adam; Nur Azlina, Mohd Fahami
Abstract : Background . Peptic ulcer is a basic term for ulcers on the lower oesophagus, stomach, or jejunum. The specific term for ulcer in the stomach is gastric ulcer. The extensive use of honey around the globe helps researchers to study the usefulness of honey. Many studies had already been conducted and proved the effectiveness of honey in treating gastric ulcer. Methods . A systematic review of the literature was conducted to identify relevant studies on honey used as an alternative treatment of gastric ulcer cause by NSAIDs. A comprehensive search was conducted in Medline, SCOPUS, and Ebscohost. The main criteria used were articles published in English and using NSAIDs-induced gastric ulcer in rat's model and those reporting the effectiveness of honey. Results . Articles published between 2001 and 2014 were identified to be relevant in studies related to the inclusion criteria. The literature search found 30 potential and closely related articles in this review, but only 5 articles were taken which meet the criteria needed to be fulfilled. Conclusions . All studies in this review reported the efficacy of honey for gastric ulcer based on its antioxidant and cytoprotective activities. Most of the studies conducted used different types of honey at various doses on rats. Future studies should be conducted to identify the appropriate dose for humans to achieve similar gastroprotective effects.